2003
DOI: 10.1303/aez.2003.49
|View full text |Cite
|
Sign up to set email alerts
|

cDNA and deduced protein sequence of acetylcholinesterase from the diamondback moth, Plutella xylostella (L.)(Lepidoptera: Plutellidae).

Abstract: The sequence of acetylcholinesterase (AChE) cDNA from the diamondback moth (DBM), Plutella xylostella (L.) was determined. A 2.3 kb partial cDNA sequence, containing an ORF encoding AChE precursor with 638 amino acid residues was obtained by primer walking. The deduced protein sequence showed the highest homology to AChE of the Colorado potato beetle (CPB) and the green rice leafhopper. The DBM AChE belongs to the Drosophila melanogaster Ace-orthologous insect AChE subfamily. A single AChE gene transcript (7.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The phylogenetic tree showed that Lepidoptera and Diptera insects are two distinct groups. This is in accord with the results based on AChE sequences of Ni et al (2003). Due to the conservation of gene sequences in closely related insects, it could be used to some extent to identify the different orders of insects or animals.…”
Section: Discussionsupporting
confidence: 86%
“…The phylogenetic tree showed that Lepidoptera and Diptera insects are two distinct groups. This is in accord with the results based on AChE sequences of Ni et al (2003). Due to the conservation of gene sequences in closely related insects, it could be used to some extent to identify the different orders of insects or animals.…”
Section: Discussionsupporting
confidence: 86%
“…Subsequently, amino acid substitutions were identified in the Cyclorrhapha fly species, Musca domestica (Huang et al, 1997;Kozaki et al, 2001;Walsh et al, 2001), Lucilia cuprina (Chen et al, 2001), and Bactrocera oleae (Vontas et al, 2002); however, no insecticide insensitivity-attributable mutation was found in Ace orthologues of the resistant strains of other insect species such as Culex pipiens (Malcolm et al, 1998), Cx. tritaeniorhynchus (Mori et al, 2001), Nephotettix cincticeps (Tomita et al, 2000) and Plutella xylostella (Ni et al, 2003). Recently, another class of AChE genes, paralogous to Ace, has been reported from the green bug, Schizaphis graminum (Gao et al, 2002) and a mosquito, Anopheles gambiae (Weill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…5Ј RACE or 3Ј RACE were also tried with gene-specific primers of the mosquito AChE, but a specific band was not obtained. It has been reported that there are long UTR promoting erroneous fusions occur during PCR in marginal regions of the AChE gene in P. xylostella (Ni et al, 2003;Baek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%